PROFISSIONAIS DA ENFERMAGEM E O MANEJO DE PACIENTES EXPOSTOS A AGROTÓXICOS - D’AVILA, TAIS CARLI (2022)
Pesticides, also known as agricultural defensives, agrochemicals or pesticides, are chemical, physical or biological substances used in the agricultural sector. Pesticides act in the control and proliferation of pests, weeds and in the fight against possible diseases associated with the cultivation of certain products. Despite the use of pesticides helping to increase crop productivity, agencies such as the World Health Organization and the National Health Surveillance Agency warn that these products are harmful to health and the environment when used incorrectly. In this sense, the present work aimed to evaluate the knowledge and preparation of nurses who are on the front line in the care and management of these patients exposed to pesticides. Interventions aimed at reducing risks and harm to the health of the population are complex to implement due to their inter-institutional nature. Since it represents an important risk factor for the health of the population, especially for the health of workers and the environment. The use of pesticides in Brazil is especially related to climatic factors. Brazil is a tropical country, with no winter periods in some regions for the pest cycle to be interrupted, as occurs in temperate and subtropical climates. Another reason is linked to the evolution that occurred in the field. The technology currently used in agriculture has allowed an increase in production. Not to mention the monoculture, widely practiced in Brazil, which also favors the cycle of pests. Currently, Brazil, in addition to being considered one of the greatest agricultural powers, is also one of the countries that consume the most pesticides in the world. According to Pesquisa Fapesp magazine, this market moves around US$ 10 billion a year in Brazil. Data from the Agricultural Census indicate that there was a 20% increase between 2006 and 2017 in rural producers using pesticides in their crops.